Faktor-Faktor Yang Mempengaruhi Minat Berwirausaha dengan Menggunakan Theory of Planned Behavior dan Perceived Desirability Dimoderasi oleh Gender (Studi Kasus Mahasiswa FEB Prodi Manajemen Universitas Harapan Medan) - Al Hafiz, Nur Salam; Nasution, Aulia Arief; Suyar, Annisa Suvero (Jurnal Ekonomi Bisnis Digital, 2022)
This study aims to determine the effect of attitude toward behavior, subjective norms, perceived behavioral control and perceived desirability on interest in entrepreneurship partially and to find out whether gender moderates the effect of attitude toward behavior, subjective norms, perceived behavioral control and perceived desirability on interest in entrepreneurship partially. The total population in this study amounted to 100 people using population research techniques. The analytical technique used is MRA. The results showed that attitude toward behavior had no effect on interest in entrepreneurship, subjective norms had a positive and significant effect on interest in entrepreneurship, perceived behavioral control had a positive and significant effect on interest in entrepreneurship, perceived desirability had no effect on interest in entrepreneurship. Gender moderates the influence of attitude toward behavior on interest in entrepreneurship, gender moderates the influence of subjective norms on interest in entrepreneurship, gender moderates the effect of perceived behavioral control on interest in entrepreneurship and gender moderates the effect of perceived desirability on interest in entrepreneurship in Management Study Program FEB students.